2021
DOI: 10.3390/nu13061863
|View full text |Cite
|
Sign up to set email alerts
|

Associations of Lifestyle Factors with Osteopenia and Osteoporosis in Polish Patients with Inflammatory Bowel Disease

Abstract: Reduced physical activity (PA), smoking, and coffee and alcohol drinking constitute risk factors of osteoporosis in patients with inflammatory bowel disease (IBD). The aim of the study was to measure the bone mineral density (BMD) and frequency of osteopenia and osteoporosis in patients with IBD and their correlation with PA, smoking, coffee, and alcohol. The study group consisted of 208 patients with IBD-103 with Crohn’s disease (CD), 105 suffering from ulcerative colitis (UC). Densitometric measurements were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 39 publications
1
14
0
Order By: Relevance
“…Therefore, a decreased bone mineral density in IBD probably stems from a number of factors, which include such elements as low BMI, malnutrition, smoking, a decreased body mass, and inflammation [2,27]. Additionally, the consumption of alcohol and coffee did not seem to affect BMD, although physical activity may prevent bone loss [28].…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, a decreased bone mineral density in IBD probably stems from a number of factors, which include such elements as low BMI, malnutrition, smoking, a decreased body mass, and inflammation [2,27]. Additionally, the consumption of alcohol and coffee did not seem to affect BMD, although physical activity may prevent bone loss [28].…”
Section: Discussionmentioning
confidence: 98%
“…BMD is one of the most important diagnostic indexes of OP. Many epidemiological studies have been conducted to investigate the connection between coffee consumption and BMD, but the conclusions are controversial ( 17 , 18 , 20 ). As a result, we used the NHANES database to perform this extensive, representative cross-sectional study.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, an increasing number of studies have found that infections or aseptic inflammatory conditions (e.g., infected osteomyelitis, septic arthritis, AIDS, rheumatoid arthritis, and inflammatory bowel disease) can contribute to the development of secondary osteoporosis (Sakurai et al, 2003;Mundy, 2007;Dapunt et al, 2015;Gallego-Escuredo et al, 2017;Rychter et al, 2021). Redlich introduced the concept of inflammatory bone loss, namely inflammation causes bone loss by disrupting bone metabolism, activating bone degradation, and inhibiting bone remodeling (Redlich and Smolen, 2012).…”
Section: Discussionmentioning
confidence: 99%